The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/tpj.14008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA‐seq analysis of nickel hyperaccumulating and non‐accumulating populations of Senecio coronatus (Asteraceae)

Abstract: Most metal hyperaccumulating plants accumulate nickel, yet the molecular basis of Ni hyperaccumulation is not well understood. We chose Senecio coronatus to investigate this phenomenon as this species displays marked variation in shoot Ni content across ultramafic outcrops in the Barberton Greenstone Belt (South Africa), thus allowing an intraspecific comparative approach to be employed. No correlation between soil and shoot Ni contents was observed, suggesting that this variation has a genetic rather than env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 85 publications
1
43
0
Order By: Relevance
“…Fe, Ni) are linked to adaptation to serpentine (Arnold et al, 2016;Bradshaw, 2005;Sobczyk, Smith, Pollard, & Filatov, 2017;Turner, Bourne, Von Wettberg, Hu, & Nuzhdin, 2010). Among these candidate genes, transporters of the Ferroportin/IREG family were shown to transport Ni in Brassicaceae and some other plant families (Halimaa et al, 2014;Meier et al, 2018;Merlot et al, 2014;Morrissey et al, 2009;Schaaf et al, 2006), and could therefore constitute a link between adaptation to ultramafic soils and Ni hyperaccumulation. The latter qualifies plants that accumulate particular metals in their leaves to levels that may be hundreds or thousands of times greater than is normal for most plants (Reeves et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fe, Ni) are linked to adaptation to serpentine (Arnold et al, 2016;Bradshaw, 2005;Sobczyk, Smith, Pollard, & Filatov, 2017;Turner, Bourne, Von Wettberg, Hu, & Nuzhdin, 2010). Among these candidate genes, transporters of the Ferroportin/IREG family were shown to transport Ni in Brassicaceae and some other plant families (Halimaa et al, 2014;Meier et al, 2018;Merlot et al, 2014;Morrissey et al, 2009;Schaaf et al, 2006), and could therefore constitute a link between adaptation to ultramafic soils and Ni hyperaccumulation. The latter qualifies plants that accumulate particular metals in their leaves to levels that may be hundreds or thousands of times greater than is normal for most plants (Reeves et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The biological functions of the identified loci and sequence variants on serpentine soils remain to be addressed. Recent comparative transcriptomics studies identified sets of genes with different overlapping orthologues in A. thaliana as more highly expressed in Ni hyperaccumulators on serpentine soil than in closely related nonaccumulator plants on other soils (de la Torre et al 2018;Meier et al 2018; van der Pas and Ingle 2019). Several DNA integrity maintenance genes were found to be more highly expressed in serpentine than in non-serpentine accessions of Senecio coronatus, but no quantitative enrichment was reported (Meier et al 2018).…”
Section: What Enables a Halleri Plants To Colonize Toxic Soils?mentioning
confidence: 99%
“…Recent comparative transcriptomics studies identified sets of genes with different overlapping orthologues in A. thaliana as more highly expressed in Ni hyperaccumulators on serpentine soil than in closely related nonaccumulator plants on other soils (de la Torre et al 2018;Meier et al 2018; van der Pas and Ingle 2019). Several DNA integrity maintenance genes were found to be more highly expressed in serpentine than in non-serpentine accessions of Senecio coronatus, but no quantitative enrichment was reported (Meier et al 2018). It must be noted that the plants compared contrast not only in their edaphic habitat, but also in the metal hyperaccumulation trait, different from A. halleri populations Noss and Pais of this study.…”
Section: What Enables a Halleri Plants To Colonize Toxic Soils?mentioning
confidence: 99%
“…Substantial intraspecific variation in Ni content can result from environmental factors, as is the case for Pimelea leptospermoides where shoot Ni contents ranging from 13 to 2873 mg kg −1 DW have been attributed to variation in total soil Ni content and pH [23]. However, in S. coronatus, this phenotypic variation has a genetic basis; plants from hyperaccumulator and non-accumulator populations have different root ultra-structures, and the accumulation phenotype of a given population persists when the plants are grown on a common soil substrate [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, two comparative RNA-Seq studies have been reported. Meier et al [24] performed a comparative RNA-Seq analysis of Ni hyperaccumulating and non-accumulating serpentine populations of S. coronatus to identify candidate genes that may underpin the Ni hyperaccumulation phenotype. A large-scale RNA-Seq study comparing seven pairs of related Ni hyperaccumulating and non-accumulating species across five families (Brassicaceae, Rubiaceae, Cunoniaceae, Salicaceae and Euphorbiaceae) from Cuba, New Caledonia and France has recently been reported [32].…”
Section: Introductionmentioning
confidence: 99%